Rozwój polskiego rolnictwa w kontekście wprowadzenia Wspólnej Polityki Rolnej - Kulka, Małgorzata; Szydło, Wiktor (Development of Polish agriculture in the context of implementation of common agricultural policy, 2006)
The article deals with the most important problems concerning financing of Polish agriculture. The principles and selected instruments of Common Agricultural Policy have been discussed. Then the latest reforms of CAP were analyzed and their influence on Polish agriculture was considered. The last section of the article is an analysis of three agricultural programs: PROW, SPO and SAPARD.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 202-214